ANALISIS NILAI TOLERANSI PADA FILM ANIMASI ZOOTOPIA - Farikhah Lely Fitria; Muhamad Taufik Hidayat (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The objective of this study was to analyze and describe the values of tolerance found in the animated film Zootopia. The method employed in this study was qualitative descriptive content analysis. Data sources were obtained from the animated film Zootopia itself. The data collection technique used was documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, as well as verification. The assessment techniques to check data validity were the credibility test, extending observation, and increasing persistence. The results of this study showed that the animated film Zootopia has six sub-values of tolerance: (1) Acknowledging the rights of every individual by providing defense for friends who still have rights in resolving the cases they are handling; (2) Granting freedom by being whatever one wants without any discriminatory attitude; (3) Agreeing on the existence of differences by coexisting with other individuals despite the differences; (4) Mutual understanding by comprehending the diversity within their environment; (5) Awareness and honesty by making the world a better place, starting with changes within oneself; (6) Tranquility and peace by providing serenity to friends in need of assistance. This study can serve as knowledge and an effective solution for instilling tolerance character values in primary school-aged children. The novelty of this study revealed the inculcation of tolerance values in the animated film Zootopia.